Mediality and Materiality in the History of Religions Journal for Religion, Film and Media - Bärbel Beinhauer-Köhler (Journal for Religion, Film and Media, 2015)
The article discusses possible terminologies for labelling historical materials. Drawing on the history of the city of Cairo around the 12th century - to the Fatimid era and to later Ayyubid times - it looks at the documents of three religions on religious infrastructure donated by women. This reveals women's ability to shape the public sphere. At least to a certain extent, the segregation of the sexes and the concept of the harem are questionable. This topic requires the reconstruction and re-reading of fragmental materials. Methodological reflections are helpful for dealing with different sources, mostly combinations of texts and archaeology, embedded in the current debate about material culture and media as well as materialization and mediation. It might seem anachronistic, but to specify these categories it is useful to compare this example with a contemporary study by Mia Lövheim on female Internet bloggers. In both cases we find women as self-confident agents in public spaces.